HOW TO ANALYSE AUTHENTICITY IN TOURISM BROCHURES: A PRAGMALINGUISTIC TOOLKIT FOR RESEARCHERS - Mohinur Ismoiljonova; Elmuradova Gulrux Karimaliyevna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. Adventure tourism brochures promise authentic experiences, yet the linguistic mechanisms behind this promise remain underexplored. This article offers a practical pragmalinguistic toolkit for researchers wishing to analyse how authenticity is constructed in promotional tourism materials. Drawing on speech act theory, deixis, implicature, and modality, the article presents a step-by-step analytical framework applicable to brochures in any language.